Inserção de tecnologias digitais como estratégia emergente de ensino e aprendizagem nos anos iniciais do ensino fundamental I - estudo de caso na EEMS Escola da Região Central Potiguar - Araújo, Maria José Souza de (Universidade Federal Rural do Semi-Árido, 2020)
The present paper is based on a discussion about the Digital Technologies Insertion in the teaching-learning process, mainly in Ensino Fundamental I (Primary School), especially in the first and second grades of this level of schooling, where it is possible to realize the need of a constructive dialogue among teachers, students, parents or guardians of the students, linked to the inclusion of these digital technologies resources in order to assist and innovate the teachinglearning process. In order to incite such discussion, it was necessary to look for the perception from some teachers of State Schools, especially in one located in the municipality of Santana do Matos/RN State. Thus, we focus the main purposes which allow us to reflect and to quest about the topic approached in this paper, among them are: to understand the significance of the technological resources in classroom, to identify how the teachers usually use the digital technologies and to notice how the technologies can influence in classroom and, as yet, to verify the usage of technologies by the students, to understand how ones apply the teacher-work intended to the new technologies, inside classrooms, and analyze how the use of these tools can contribute to the cognitive development of those students. As yet, one adds that the present study intends to recognize the significance of the insertion of digital technologies in this process as a facilitator method of learning in first grades of Ensino Fundamental I (primary School). In order to achieve the proposals already referred before (in these lines), it has been done an exploratory research with that related school teachers and also in a bibliographical character on some ancient books and on published works in order to allow the confirmation of the hypothesis and make the question evident. One emphasizes that the present paper is based on the conception of some theorists that will lead us to the reflections about the discussion of the insertion of digital technologies in classroom, as: Moran (2000), Libâneo (2007), Sobral (1999) e Otto (2016). As effect, ones understood that, in consensus, educators when questioned they see the insertion of technologies in classroom as a preponderant factor to instruction and the cognitive development of the kids, a proposal in order to instigate the capacitation/education about the active digital technologies, for teachers, in a way that will be possible the acquisition and enlargement of knowledge, by creating environments of learning and facilitating the development of the intellectual process of students inside and out of classroom.
Monografia
Keywords: Ensino Fundamental I; Tecnologias digitais; Ensino e aprendizagem; Inovação; Ensino Fundamental I; Digital technologies; Teaching and learning; Innovation; CIENCIAS EXATAS E DA TERRA::COMPUTACAO E INFORMATICA